2022
DOI: 10.1186/s12941-022-00533-3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and capsaicin regulate apoptosis and alleviate intestinal inflammation induced by Clostridioides difficile in vitro

Abstract: Background The dramatic upsurge of Clostridioides difficile infection (CDI) by hypervirulent isolates along with the paucity of effective conventional treatment call for the development of new alternative medicines against CDI. The inhibitory effects of curcumin (CCM) and capsaicin (CAP) were investigated on the activity of toxigenic cell-free supernatants (Tox-S) of C. difficile RT 001, RT 126 and RT 084, and culture-filtrate of C. difficile ATCC 700057. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 88 publications
3
20
0
Order By: Relevance
“…In addition, we demonstrated here that capsaicin can reduce IFN-γ, and IL-6 levels, which has not been shown before. This builds on previous studies that have shown the anti-inflammatory effects of capsaicin in human colon cancer cell lines [60] and porcine epithelial cell lines [59]. Interestingly, we did not see any major effects of IL-8 levels, which was inhibited, albeit minimally, in previous studies utilizing an LPS-induced inflammatory response in porcine epithelial cells [59].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we demonstrated here that capsaicin can reduce IFN-γ, and IL-6 levels, which has not been shown before. This builds on previous studies that have shown the anti-inflammatory effects of capsaicin in human colon cancer cell lines [60] and porcine epithelial cell lines [59]. Interestingly, we did not see any major effects of IL-8 levels, which was inhibited, albeit minimally, in previous studies utilizing an LPS-induced inflammatory response in porcine epithelial cells [59].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we used the toxigenic strain of C. difficile RT001 (A + B + ), which was previously characterized in the Department of Anaerobic Bacteriology in Research Institute for Gastroenterology and Liver Diseases in Tehran, Iran [ 34 ]. The strain was cultured on cycloserine-cefoxitin-fructose agar (CCFA, Mast) supplemented with 5% (v/v) sheep blood under anaerobic conditions (85% N 2 , 10% CO 2 and 5% H 2) (Anoxomat® Gas Exchange System, Mart Microbiology BV) at 37 °C for 48–72 h after an alcohol shock treatment [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Tox-S preparation was carried out as described previously [ 36 ]. In brief, the C. difficile RT001 was grown anaerobically in CCFA for 48 h and then used to prepare a bacterial suspension equal to 2 McFarland turbidity standard in 0.85% sterile saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations